The importance of thigh strength in basketball and volleyball - Dervisevic, M.; Rado, I.; Dervisevic, E.; Hadzic, V. (Sport Science - International Scientific Journal of Kinesiology, 2015)
Systematic isokinetic evaluation of the knee joint in the preparation period is very useful in highlighting the risks for athletes in case of injury quadriceps and hamstring. Isokinetic evaluation of the strength of the quadriceps (Q) and hamstring (H), during the concentric (con) and eccentric (ECC) mode muscle contraction, is an important part of a comprehensive evaluation and rehabilitation of athletes. The main purpose of this communication is to present the main invention of various studies relating to this question.